Prevalence and Factors Associated with Unsafe Abortion Among Women Admitted on the Gynaecological Ward of Kabale Regional Referral Hospital. - Opeto, Moses (Kabale University, 2024)
Unsafe abortion in Uganda is common and is among the major contributors to maternal mortality and morbidity. Its management and treatment consume large amounts of the already scarce health system resources, yet little is known about its prevalence and associated factors. The aim of this study was to determine the prevalence and factors associated with unsafe abortion among women admitted to the gynaecological ward of Kabale Regional Referral Hospital, in South Western Uganda. Methods This was a hospital-based cross-sectional study among 227 mothers admitted with abortion-related conditions in the gynaecological ward of Kabale Regional Referral Hospital. Results The prevalence of unsafe abortion in this study was 7%. Factors associated with unsafe abortion were being a student (AOR=74.3, 95% CI 4.70-1176at p-value of 0.002), being referred from lower level health facility (AOR=10.77, 95% CI:1.81-64.83 at p-value 0.009) Conclusion and recommendations The prevalence of unsafe abortion in the study population is high. Being a student and being referred from a lower health facility were strongly associated with having unsafe abortion. We recommend further studies to understand factors regarding unsafe abortion specifically among students and lower health centres.